Locally Structured On-Chip Optofluidic Hollow-Core Light Cages for Single Nanoparticle Tracking - Kim, Jisoo; Foerster, Ronny; Wieduwilt, Torsten; Jang, Bumjoon; Buerger, Johannes; Gargiulo, Julian; Menezes, Leonardo De S.; Rossner, Christian; Fery, Andreas; Maier, Stefan A.; Schmidt, Markus A. (ACS Sensors, 2022)
Nanoparticle tracking analysis (NTA) is a widely used methodology to investigate nanoscale systems at the single species level. Here, we introduce the locally structured on-chip optofluidic hollow-core light cage, as a novel platform for waveguide-assisted NTA. This hollow waveguide guides light by the antiresonant effect in a sparse array of dielectric strands and includes a local modification to realize aberration-free tracking of individual nano-objects, defining a novel on-chip solution with properties specifically tailored for NTA. The key features of our system are (i) well-controlled nano-object illumination through the waveguide mode, (ii) diffraction-limited and aberration-free imaging at the observation site, and (iii) a high level of integration, achieved by on-chip interfacing to fibers. The present study covers all aspects relevant for NTA including design, simulation, implementation via 3D nanoprinting, and optical characterization. The capabilities of the approach to precisely characterize practically relevant nanosystems have been demonstrated by measuring the solvency-induced collapse of a nanoparticle system which includes polymer brush-based shells that react to changes in the liquid environment. Our study unlocks the advantages of the light cage approach in the context of NTA, suggesting its application in various areas such as bioanalytics, life science, environmental science, or nanoscale material science in general.
CRIS-Team Scopus Importer:2023-03-20
Keywords: colloidal analytics; integrated photonics; nanoparticle tracking analysis; optofluidics; waveguiding